Cobalt-rich diagenetic Mn-oxide mineralization in the neogene onshore Pisco Basin, Peru - Carcamo-Valencia, Ivana C. (2025)
Sedimentary basin-hosted manganese oxides may represent an important yet underexplored source of critical metals. Here we present a stratigraphic, textural, mineralogical, and compositional characterization of Mn-oxide nodules, coatings, and veins in the Pisco onshore forearc basin, Peru. The Mn-oxide mineralization is stratabound within marine sandstone, siltstone, and tuff from the Neogene Chilcatay and Pisco formations. X-ray diffraction and electron microprobe analyses identify the Mn oxides as cryptomelane (± hollandite) and todorokite, which cement detrital grains and fossilize biological remains. Bulk chemical analyses of nodules, coatings, and veins reveal significant cobalt enrichment (mean = 0.17 ± 0.15 wt% Co; up to 0.63 wt% Co), corroborated by electron probe microanalysis of individual Mn oxide phases (mean = 0.37 ± 0.33 wt% Co; up to 2.1 wt% Co). The stratigraphic control, biomorphic replacement, mineralogy, and chemical composition collectively indicate a diagenetic origin for the Mn-oxide mineralization. The formation pathway likely involved organic matter decay or brine-hydrocarbon interactions coupled with Mn and Fe reduction, resulting in metal-enriched porewaters that circulated along structures and permeable horizons. Subsequent precipitation under oxygenated conditions occurred during late Pliocene uplift and exposure of the East Pisco Basin. This study demonstrates that diagenetic Mn oxides exposed in onshore basins represent a potential resource for manganese and critical elements such as cobalt.